The Implementation Result of Comparative Method in the Instruction of Rural Development for Political Students at the Faculty of Education, Souphanouvong University; Academic Year 2020-202: https://doi.org/10.69692/SUJMRD1004155 - KHOTSAIGNO, Saiphone; OUDOMSITH, Houmpheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research intended to evaluate the result of an instruction by using comparative local visit method for Rural development subject, which a subject of political students at the faculty of Education, Souphanouvong University; The research aimed to investigate the learning progress after leading student to conduct a local visit and learn from the real situation with local authority. The sample of research is targeted on the political students whom are the only one group to have the subject of Rural development in the curriculum with totally number of 5858 person with 2727 females included. The data collection is conducted by using the pretest and posttest to evaluate their learning progress difficulty level ranged between 0.40-0.86; and the reliability was of .84. The research found that the result of posttest after local visit is higher than the pretest in the class room with the significant level of.05; the learning progress of the students whom comes from different resident are not significant different; Student has very good attitude with the comparative method with learning by local visit.